Analysis Of Problem-Solving Skills Related To Building Space Material In Students At Smp Negeri 2 Galesong Selatan - Wibowo, Ari; Lasarus, Marilyn (Eduscape : Journal of Education Insight, 2024)
This study aims to describe how students' problem-solving abilities use Polya stages in completing space building material. The research method is descriptive qualitative. The subjects of this study were taken by 3 students from 27 students of grade VIII.f SMP Negeri 2 Galesong Selatan. Based on the results of the study, it can be concluded that the ability to solve mathematical problems to solve the material to build space with the Polya stage is a high-ability student, that is, students are able to meet the problem-solving indicators even though there are some indicators that are not written down but can be explained at the interview, and it does not mean that students are not able to solve the problem. It's just that students don't want to be complicated and rewrite which in the end is rewritten in the next indicator. Students with moderate ability, namely students are able to meet the indicators of problem solving, but there are some students who misunderstand the concept of solving problems, because they do not match what is planned with what is written in solving problems because students are in a hurry to solve problems. Low-ability students, namely students are only able to meet 2 indicators because they do not understand the plan to be used in solving the problem.